Relationship Between HIV Coinfection, Interleukin 10 Production, and Mycobacterium tuberculosis in Human Lymph Node Granulomas. (26th July 2016) - Diedrich, Collin R.; O'Hern, Jennifer; Gutierrez, Maximiliano G.; Allie, Nafiesa; Papier, Patricia; Meintjes, Graeme; Coussens, Anna K.; Wainwright, Helen; Wilkinson, Robert J.
Abstract: Background.  Human immunodeficiency virus type 1 (HIV)–infected persons are more susceptible to tuberculosis than HIV–uninfected persons. Low peripheral CD4 + T-cell count is not the sole cause of higher susceptibility, because HIV–infected persons with a high peripheral CD4 + T-cell count and those prescribed successful antiretroviral therapy (ART) remain more prone to active tuberculosis than HIV–uninfected persons. We hypothesized that the increase in susceptibility is caused by the ability of HIV to manipulate Mycobacterium tuberculosis –associated granulomas. Methods.  We examined 71 excised cervical lymph nodes (LNs) from persons with HIV and M. tuberculosis coinfection, those with HIV monoinfection, and those with M. tuberculosis monoinfection with a spectrum of peripheral CD4 + T-cell counts and ART statuses. We quantified differences in M. tuberculosis levels, HIV p24 levels, cellular response, and cytokine presence within granulomas. Results.  HIV increased M. tuberculosis numbers and reduced CD4 + T-cell counts within granulomas. Peripheral CD4 + T-cell depletion correlated with granulomas that contained fewer CD4 + and CD8 + T cells, less interferon γ, more neutrophils, more interleukin 10 (IL-10), and increased M. tuberculosis numbers. M. tuberculosis numbers correlated positively with IL-10 and interferon α levels and fewer CD4 + and CD8 + T cells. ART reduced IL-10 production. Conclusions.  Peripheral CD4 + T-cell depletion correlated with increased M. tuberculosis presence, increased IL-10 production, and other phenotypic changes within granulomas, demonstrating the HIV infection progressively changes these granulomas.